2017
DOI: 10.33378/jppik.v11i1.84
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Air dan Beban Limbah Karamba Jaring Apung di Waduk Jatiluhur Jawa Barat

Abstract: Penelitian ini telah dilakukan mulai bulan April sampai Juli 2016 di Waduk Jatiluhur, Kabupaten Purwakarta. Tujuan Penelitian untuk mengetahui status kualitas perairan waduk Jatiluhur yang digunakan untuk budidaya Keramba Jaring Apung dan mengetahui beban limbah yang berasal dari keramba jarring apung. Diharapkan informasi ini dapat ditentukan kualitas perairan waduk jatiluhur dan apakah beban limbah yang berasal dari KJA sudah melampaui kapasitas asimilasi ekosistem waduk tersebut. Jenis data yang dikumpulkan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The large number of floating net cages results in the large number of fish feeds that are poured every day. Fish feed in the form of pellets used by farmers has the main content in the form of nitrogen and phosphorus [22]. Fish feed that is not absorbed by fish becomes a burden on aquatic waste which results in high phosphate concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The large number of floating net cages results in the large number of fish feeds that are poured every day. Fish feed in the form of pellets used by farmers has the main content in the form of nitrogen and phosphorus [22]. Fish feed that is not absorbed by fish becomes a burden on aquatic waste which results in high phosphate concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…KJA units also function as residences and stalls, thus generating domestic waste from bathing, washing, latrines and garbage activities. The results showed that the water quality status of the Jatiluhur reservoir based on "US-EPA" was moderately polluted, almost heavily polluted, with a value of -30 class C (Anas et al, 2017). Furthermore, Prinajati (2019) reported that fish farming activities in cages reduced water quality and increased the water pollution load by 512.89 mg/second.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the problems that occur, research is needed regarding the current description of the water quality of the Jatiluhur Reservoir. Several studies on water quality in Jatiluhur Reservoir have been conducted (Anas et al, 2017;Hamzah et al, 2016;Prinajati, 2019). However, water quality must be described in detail, considering that different biogeochemical reactions occur at each of those depths.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, UKM juga berperan menyumbangkan limbah seperti Keramba Jaring Apung (KJA) yang terdapat di perairan Waduk Jatiluhur menjadi penyebab penurunan kualitas air sebesar 7,87% antara tahun 2014 dan 2019 (Prinajati, 2019). Pencemaran di Waduk Jatiluhur didominasi oleh limbah bahan organik dari populasi keramba jaring apung yang sudah melebihi batas misal dari sisa pakan ikan (Anas, Jubaedah, & Sudino, 2017).…”
Section: Pendahuluanunclassified